A survey of East Palaearctic Lycosidae (Araneae). 9. A review of Sibirocosa with a description of three new species - Omelko, Mikhail M.; Marusik, Yuri M. (Zootaxa, 2013)
The East Palaearctic genus Sibirocosa Marusik, Azarkina & Koponen, 2004 is surveyed and three species S. koponeni sp. n. (Maritime Province), S. nadolnyi sp. n. and S. trilikauskasi sp. n. (both from Khabarovsk Province) are described from the Russian Far East. Illustrations to all six species found in East Asia are provided.